Perceived quality of traditional grocery stores: price satisfaction, trust, service quality, convenience and location - Nurliza, Nurliza (Serbian Journal of Management, 2025)
Perceived quality is a crucial factor in influencing purchase intention. Unfortunately, a utilitarian, unidimensional model is inadequate, has divergent perceived values, and ignores emotional dimensions. To examine the concurrent effects of price satisfaction, trust, service, convenience, and location on households’ perceived quality in traditional grocery stores, the study used a multidimensional concept. The study employed mixed methods for 183 households, utilizing non-probability sampling with SmartPLS. Partial least squares modeling was utilized to evaluate the cause-and-effect relationships between price satisfaction, trust, service quality, convenience, and location on perceived quality using cue utilization theory via multidimensional concept. Household perceptions of quality are more likely to be positively correlated with rising service quality, which is followed by location, price satisfaction, and trust. But because of the reputation and trust of the store, convenience is eroding. The most crucial elements in service quality, price satisfaction, trust and location, and convenience are, in that order, tangibleness, price confidence, credibility, accessibility to the location by public transit, and ease of use. The impact of service quality on pricing satisfaction is significant, whereas its influence on perceived quality is very minor. Perceived quality is substantially affected by pricing satisfaction, trust, convenience, location, and service quality.